Penyuluhan Peningkatan Kualitas Tidur pada Lansia di ILP Kelurahan Arjosari Kota Malang - Ghaida Ghaida; Zidni Imanurrohmah Lubis; Fika Ertitri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Aging is often accompanied by sleep problems that have a negative impact on the well-being of older adults, such as reducing their quality of daily life and triggering a higher risk of chronic diseases, depression, and cognitive decline. To address this issue, the physiotherapy team held an educational program at the Arjosari Village ILP in Malang City, which aimed to equip older adults with knowledge about the value of quality sleep. The material was delivered through simple brochures, two-way discussion sessions, and assessments through initial and final tests. A total of 15 people participated, and from the opening discussion, about 80 percent of them admitted to having frequent sleep disturbances. Before the event, a survey showed that their understanding was still minimal, especially regarding what healthy sleep is, the triggers of sleep disturbances, the benefits of good sleep, the signs of sleep disturbances, and steps to overcome them. After the counseling, there was a significant increase, with the level of understanding reaching more than 86 percent on all topics. These results prove that community-based educational approaches such as this are very effective as a means of empowerment and early prevention. Activities such as this should be made a routine to support the overall health of the elderly.